2019
DOI: 10.1155/2019/6402097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Premorbid Psychiatric Disorder on the Incidence of Delirium during ICU Stay, Morbidity, and Long-Term Mortality

Abstract: Introduction. Delirium during ICU stay is a widespread problem with complex aetiology. A premorbid psychiatric disorder has been associated with an increased incidence of delirium in the general hospital population, but data on the impact of ICU delirium and consequences for morbidity and long-term mortality remain scarce. Methods. In this single-centre retrospective analysis, 472 patients with an ICU stay >48 hours were included during a 2-year period. Postresuscitation and neurosurgical patients were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“…On the other hand, in another study of veterans by the same group, involving critically ill medical patients, crude hospital mortality was lower among those with mental disorders (7.3% vs. 8.7%, respectively), but higher on adjusted analysis (OR: 1.07; 95% CI: 1.01 - 1.14), though similar at 30-day (OR: 1.01; 95% CI: 0.94 - 1.08) [ 33 ]. Finally, in a single-center study from the Netherlands, unadjusted hospital morality was lower among critically ill patients with mental disorders that those without this diagnosis (9.7% vs. 13.3%, respectively), but the difference was not statistically significant, likely due to the small cohort size [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in another study of veterans by the same group, involving critically ill medical patients, crude hospital mortality was lower among those with mental disorders (7.3% vs. 8.7%, respectively), but higher on adjusted analysis (OR: 1.07; 95% CI: 1.01 - 1.14), though similar at 30-day (OR: 1.01; 95% CI: 0.94 - 1.08) [ 33 ]. Finally, in a single-center study from the Netherlands, unadjusted hospital morality was lower among critically ill patients with mental disorders that those without this diagnosis (9.7% vs. 13.3%, respectively), but the difference was not statistically significant, likely due to the small cohort size [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings prompted the investigators to hypothesize that mental disorders may predispose patients to critical illness [ 14 ]. Mental disorders were reported in 6.2% [ 14 ] to 36.4% [ 15 ] of ICU patients in the general population and studies on the association between mental disorders and short-term mortality showed either no difference [ 16 ] or increased risk of death [ 17 ], as compared to those without mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Delirium refers to altered consciousness and cognition with an acute onset and a fluctuating course. 1 Its prevalence in intensive care units (ICU) varies from 4% to 89%. 2,3 Delirium is specifically prevalent among patients under mechanical ventilation so that more than 80% of these patients experience delirium.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Delirium is specifically prevalent among patients under mechanical ventilation so that more than 80% of these patients experience delirium. 1,4,5 A study reported that delirium increased the length of hospital stay by 3.45 so that the length of hospital stay among patients with and without delirium was eleven and seven days, respectively. Moreover, delirium increased the risk of death by 2.43 times.…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating the association between mental disorders before ICU admission and ICU delirium occurrence have reported conflicting results and have important limitations (8)(9)(10)(11). Study populations have been small, the presence of anxiety and/or depression has not been rigorously evaluated, trained evaluators have not conducted delirium assessments, and the presence of established baseline and ICU daily factors for delirium has not been rigorously considered.…”
mentioning
confidence: 99%